Gut Bifidobacteria Populations in Human Health and Aging - Arboleya, Silvia; Watkins, Claire; Stanton, Catherine; Ross, R. Paul (Frontiers in Microbiology, 2016)
The intestinal microbiota has increasingly been shown to have a vital role in various aspects of human health. Indeed, several studies have linked alterations in the gut microbiota with the development of different diseases. Among the vast gut bacterial community, Bifidobacterium is a genus which dominates the intestine of healthy breast-fed infants whereas in adulthood the levels are lower but relatively stable. The presence of different species of bifidobacteria changes with age, from the childhood to old age. Bifidobacterium longum, Bifidobacterium breve and Bifidobacterium bifidum are generally dominant in infants whereas Bifidobacterium catenulatum, Bifidobacterium adolescentis and, as well as B. longum are more dominant in adults. Increasingly, evidence is accumulating which shows beneficial effect of supplementation with bifidobacteria for the improvement of human health conditions ranging from protection against infection to different extra- and intra-intestinal positive effects. Moreover, bifidobacteria can be associated with the production of a number of potentially health promoting metabolites including short chain fatty acids, conjugated linoleic acid and bacteriocins. The aim of this mini-review is to describe the bifidobacteria composition changes associated with different stages in life, highlighting their beneficial role, as well as their presence in commonly known disease states.